Quality Health Improvement Using GEN SMART Mendala in Mendala Village - Richa Amalia; Hangge Daud Wahyudi; Sunarto; Erwin Hendra Putra (Indonesian Journal of Social Responsibility Review (IJSRR), 2023)
Indonesia, a country with a population of 281 million, poses a big challenge in managing public health. Currently Indonesia is facing a triple burden of various disease problems, Indonesia is also experiencing another health burden, namely stunting. Stunting is not only a matter of height but the most dangerous thing is the child's low ability to learn, mental retardation, and the third is the emergence of chronic diseases. The President of Indonesia in the BKKBN National Working Meeting stated that, "The existing infrastructure and institutions, he continued, must be mobilized to make it easier to solve the problem of stunting. From the environment, starting from clean water, sanitation, healthy housing, this is an integrated work and must be consolidated. The method used is Participatory rural appraisal (PRA). The purpose of this study was to determine the impact of the active participation of PT Pertamina Hulu Energi Ogan Komering in handling stunting through the "Healthy Prosperous Generation Mendala Village (Gen Smart Mendala)" Program. As a result, GEN SMART Mendala obtained an IKM score of 3.81 with a GOOD predicate from the people of Mendala Village who were the program's targets